Comparison of Clinical Scores for Predicting Stroke‐Associated Pneumonia After Acute Ischemic Stroke - Linlin Wang; Jun Xu; Xinyu Liu; Feifei Ma; Xingquan Zhao; Anxin Wang; Ruijun Ji; Yongjun Wang; CNSR III investigators (Aging Medicine)
ABSTRACT Objectives To compare the discrimination and calibration of six risk scoring systems in the assessment of patients with stroke‐associated pneumonia (SAP) after acute ischemic stroke. Methods The validation cohort was derived from the Third China National Stroke Registry. SAP was diagnosed according to the criteria for hospital‐acquired pneumonia of the Centers for Disease Control and Prevention. The area under the receiver operating characteristic curve (AUROC) and Hosmer‐Lemeshow goodness‐of‐fit test were used to assess discrimination and calibration. Results A total of 12,071 patients were included in the study and 606 (5.02%) patients were diagnosed with in‐hospital SAP after ischemic stroke. The AUROC of the six clinical scores ranged from 0.660 to 0.752. In the pairwise comparison, the AIS‐APS score (0.752, 95% CI = 0.730–0.773, p < 0.001) showed significantly better discrimination than the other risk models, except the PASS score. The AIS‐APS score had the largest Cox and Snell R 2 for in‐hospital SAP after ischemic stroke. In the subgroup analysis, among patients over 61 years of age, all TOAST subtypes except small vessel disease, length of hospital stay longer than 8 days, male and female sex, different groups stratified by admission NIHSS score and time from onset to arrival, the AIS‐APS score showed better discrimination than other risk models with regard to SAP after AIS. Conclusions Our study compared the discrimination and calibration of the Kwon Pneumonia Score, A2DS2 score, PANTHERIS score, AIS‐APS score, ISAN score, and PASS score in SAP identification; of these, the AIS‐APS score showed the best performance.